Characteristics of Immunopathological Changes with Nephrotic Syndrome in Children with Lymphatic Diathesis - Искандарова Ирода Рустамовна; Шарипова Инобат Сапабаевна; Абдурасулов Абдулла Кудратович (Scholars Digest Publishing, 2023)
Glomerulonephritis (GN) is a genetically determined immune-mediated inflammation with a predominant lesion of the glomeruli and the involvement of all renal structures in the pathological process, clinically manifested by renal and extrarenal symptoms. In a number of parenchymal kidney diseases, GN occupies a dominant place, in which chronic glomerulonephritis (CGN) is more than 35% and is one of the common causes of chronic renal failure (CRF). The main manifestation of the nephrotic form of glomerulonephritis is nephrotic syndrome (NS), which is characterized by proteinuria (more than 2.5 g / day or 50 mg / kg body weight), oliguria, edema, hypoproteinemia, hypoalbuminemia, hyperlipidemia, hypercoagulation and develops as the main manifestation of acute and chronic glomerulonephritis. Currently, the problems of progression of steroid-resistant, steroid-dependent and often recurrent forms of CGN in children remain one of the topical issues in the world pediatric nephrology, which is determined by the high incidence of CRF, observed by more than 50% of patients within 5-10 years. Therefore, from a clinical point of view, it is extremely important to search for clinical and immunological predictors of an unfavorable renal outcome, which make it possible to predict the course diseases with an individual assessment of the risk of developing chronic renal failure. In this regard, attention is paid to the nephrotic form of CGN in children against the background of lymphatic diathesis.